Spatial and statistical analysis of surface water in the valley Shor up basin, east of Wasit Governorate - Ali Hussein Salman Mashkur; Dr. ABBAS FADIL ABED AL-QARAGHOLI (Journal of College of Education, 2025)
This study focused on the most prominent physical and chemical characteristics of the valley Shor up basin in Wasit Governorate, using geographic information systems, and their role in pollution of the valley stream, which has an area of ​​(474.6) km2. For the purpose of identifying the characteristics of surface water, temporally and spatially, (25) models of (10) Various locations on the basin’s course. Chemical analyzes were conducted for the purpose of knowing the hydrochemical properties of the surface water present in the study area, which include positive and negative ions, as well as determining the hydrochemical formula of this water. These characteristics were represented by a study of: (Temperature, turbidity, pH, dissolved solids, total hardness, electrical conductivity, total basicity, calcium ion, magnesium, sodium, potassium ion, carbonates, bicarbonates, sulfates, chlorides, nitrates, phosphates, manganese, zinc, iron, cadmium, copper, lead, boron), In light of these data, the results of laboratory analysis showed that there is a spatial variation in surface water concentrations, and this variation is due to the increase in drainage rates and the abundance of suspended materials in the water resulting from rainwater, the sweeping of soil, and its arrival into the riverbed. The statistical methods used in this field are calculating the correlation coefficient. And the factor analysis (Factor analysis), the results of the correlation coefficient showed that no very strong inverse correlation was recorded from the elements, as well as a strong correlation between them for the water of the study area. As for the factor analysis, five factors were reduced and included about (91.01%) of the variance in the original variables, which is the percentage Very high indicates that the majority of the data that entered the analysis was included in the interpretation process.